Blaťácké Zlato Cheese: A Screenshot of Its Biofunctional and Physicochemical Characteristics - Sandra T. Martín-del-Campo; Alexa Pérez-Alva; Sheba Sunny-Marottickal; Michaela Freyová; Tomáš Kudera; Iveta Klojdova; Diana K. Baigts-Allende (Foods, 2025)
This study aims to determine the Blaťácké zlato cheese in vitro antioxidant activity and its correlation with specific peptides. A general physicochemical evaluation was also conducted, considering possible differences between batches. The antioxidant activity focused mainly on the nitrogen fractions with the shortest-chain peptides. Other parameters were evaluated, including color, weight, size, moisture, dry matter, and texture analysis, which included the whole cheese hardness and the texture profile analysis. The ethanol soluble (EtOH-SN) and non-protein nitrogen (NPN) fractions were selected to evaluate antioxidant activity by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) methods, total phenol content (TPC), and peptide profiles. Our findings revealed significant differences between batches for NPN ABTS activity and EtOH-SN TPC. Significant differences were observed for water activity, moisture, dry matter, moisture on fat-free basis (MFFB), and pH in the central surface. DPPH and TPC showed a similar behavior, and NPN showed higher values than the EtOH-SN fraction. However, the opposite was observed for ABTS. Significant correlations were found for the biological activities with individual peaks of their corresponding HPLC peptide profiles. Finally, the principal component analysis separated the cheeses according to the batch, mainly due to specific peptides.